Formation of Protein Disulfide Bonds Catalyzed by OsPDIL1;1 is Mediated by MicroRNA5144-3p in Rice. (28th November 2017) - Xia, Kuaifei; Zeng, Xuan; Jiao, Zhengli; Li, Maolin; Xu, Weijuan; Nong, Quandong; Mo, Hui; Cheng, Taihui; Zhang, Mingyong
Abstract: Correct folding of proteins in the endoplasmic reticulum is important for their stability and function under stress. The protein disulfide isomerase (PDI) OsPDIL1;1 is a key protein-folding catalyst in rice ( Oryza sativa L.). Here, microRNA5144 (osa-miR5144-3p) is reported to mediate the formation of protein disulfide bonds via targeting OsPDIL1;1 mRNA in rice seeds and seedlings during development and under conditions of abiotic stress, respectively. Expression analysis of transgenic rice and identification of cleavage sites showed that OsPDIL1;1 mRNA is a target of osa-miR5144-3p. Expression of osa-miR5144-3p and OsPDIL1;1 was shown to be inversely regulated in developing organs and under abiotic stress. The down-regulation of osa-miR5144-3p or overexpression of OsPDIL1;1 in transgenic rice showed increased total protein–disulfide bond content, compared with the wild type. This indicates that protein–disulfide bond formation is enhanced by down-regulation of osa-miR5144-3p or overexpression of OsPDIL1;1 . These transgenic rice plants also displayed strong resistance to salinity and mercury stress, in comparison with the wild type. In contrast, the transgenic rice plants overexpressing osa-miR5144-3p or down-regulating OsPDIL1;1 had a lower protein–disulfide bond content; they were susceptible to abiotic stress and produced abnormal grains with small and loosely packed starch granules. These results indicate that protein–disulfide bond formation catalyzed by OsPDIL1;1 is modulated by osa-miR5144-3p in rice during development and is involved in resistance to abiotic stress.